Characterization of the phthalate acid catabolic gene cluster in phthalate acid esters transforming bacterium-Gordonia sp. strain HS-NH1. (January 2016) - Li, Dandan; Yan, Jiali; Wang, Li; Zhang, Yunze; Liu, Deli; Geng, Hui; Xiong, Li
Abstract: In this work, strain HS-NH1 which utilized phthalate acid esters (PAEs) as sole carbon and energy sources for growth, was isolated and identified as Gordonia sp. Phthalate acid (PA) and protocatechuate acid (PCA) were the major intermediate products by HPLC analysis. The phthalate acid catabolic gene cluster ( phtBAabcdCR ) which is responsible for the conversion of PA into PCA in strain HS-NH1 was obtained by genome analysis. The phtB, phtAab, phtAcd and phtC genes were expressed in Escherichia coli . Mixture of PhtAab and PhtAcd were able to convert PA into a product, which was then transformed to PCA by mixture of PhtB and PhtC. The enzymatic results as well as homology analysis of phtBAabcdCR gene sequences demonstrated that phtAabcd encodes the 3, 4-phthalate dioxygenase which consists of three components: a hetero-oligomeric oxygenase, a [3Fe-4S]-type ferredoxin, and a GR-type reductase. PA was oxidized by 3, 4-phthalate dioxygenase, subsequently transformed into PCA by dihydrodiol dehydrogenase (PhtB) and dihydroxyphthalate decarboxylase (PhtC). This study firstly reports the characterization of pht operon in Gordonia sp. Highlights: First report of characterizing pht gene cluster in Gordonia sp. A pht gene cluster was obtained by genome sequencing. The phtB, phtAab, phtAcd and phtC genes were expressed in E. coli BL21 (DE3).